What is the fate of Retirees? Payment of Contributory Pension Scheme and the Welfare of Public Service Retirees in Selected States of Southwest, Nigeria - Lawal Bakare; Dauda Morakinyo (Universitas Negeri Semarang, 2025)
The study examined the initial lump-sum payment under the Contributory Pension Scheme and its implications for the welfare of public service retirees in selected states of Southwest Nigeria. Primary data were collected from 1,850 pensioners in Osun, Ondo, and Ogun States using structured questionnaires and interview schedules, and were analysed descriptively and inferentially. The findings indicate that lump-sum payments are generally insufficient to meet retirees’ basic post-retirement needs, including healthcare, food, shelter, and other welfare requirements, particularly amid inflation and the rising cost of living. Administrative inefficiencies, corruption, and inequalities in benefit distribution further increase retirees’ vulnerability, with lower-cadre workers more adversely affected than politically or institutionally connected elites. The study concludes that, although the Contributory Pension Scheme was designed to promote sustainability and transparency, it has not adequately provided social security for many retirees. The study recommends timely payment of lump sums and death benefits, stronger accountability measures, effective enforcement of sanctions, technological innovations, inflation-adjusted benefits, and targeted empowerment programmes. The study contributes to pension reform literature by highlighting the need to balance fiscal sustainability with human security, equity, and fairness.